Low energy dissipation readout of single-molecule ferroelectronic states by a spin-Seebeck signal - Hua-Hua Fu; Dan-Dan Wu; Gui-Fang Du; Qing-Bo Liu; Menghao Wu (Physical Review Research, 2020)
Single-molecule magnets (SMMs) possessing bistable states have been considered as promising candidates to realize zero-dimensional (0D) ferroelectrics (FE) and multiferroics (MF) with high storage density. However, how to read or manipulate the FE states with low-energy-dissipation strategy is still a hard challenge. Here, we intercalated a magnetic metal porphyrin molecule, such as TiP with switchable vertical electric polarization, within the MoS_{2} bilayer to realize 0D FE states. First-principles calculations show that the MoS_{2} monolayer contacted by SMMs is spin polarized to provide two spin-dependent transport tunnels. As a temperature gradient is applied along the transport channels, a well-defined spin-Seebeck effect (SSE) occurs in the spin-polarized MoS_{2} layer, helping to generate a pure thermal spin current. More importantly, the spin-Seebeck signal is associated tightly with the FE state in the same layer, and both of them can be switched simultaneously to another layer by an external electric field. The theoretical results not only put forwards a low-energy-dissipation strategy to read the SMM-based FE states, but also develop a new research field of spin-ferroelecto-caloritronics, which focuses on the interplay of electrons' spin and FE states in the presence of a temperature gradient.